The Auditor-Firm Conflict of Interests: Its Implications for Independence: A Reply. - Goldman, Arieh; Barlev, Benzion (The Accounting Review, 1975)
This article presents response of the author on comments made by scholars Nissim Aranya and Moshe Sarell on the paper "The Auditor-Firm Conflict of Interests: Its Implications for Independence" that was published in the October 1974 of the periodical "The Accounting Review." Students of the professions have traditionally focused on two types of issues. The first relates to the ability of the profession to become free of lay control, to be self-directing in matters such as recruitment, education, certification, and the policing of membership's professional behavior. This area of research is often known as professionalization, or professional autonomy, and has received most of the attention of students of the professions. Indeed, the list of references cited by Aranya and Sarell in their comment covers only a small part of this vast literature. The second area of research is concerned with deviations by professionals from professional rules of conduct as a result of pressures by clients and of various conflicts of interests.